Pembelajaran Berbantuan Komputer (PBK) Pada MIN Pahandut dan MIN Langkai Kota Palangka Raya - Azis, Abdul (LP2M IAIN Palangka Raya, 2009)
The purpose of this study is to find out the implementation of computer asissted instruction at MIN Pahandut and MIN Langkai Palangka Raya. The study used qualitative approach. The object of this study was the instructional process by using computer asissted instruction. The subjects of the study were teachers and students that used CAI (Computer-Assisted Instruction). Data were taken by using observation, interview, and documentation technique. To analyse the data used the qualitative descriptive analysis which used Miles and Hubermanâs model. They were reduction, display, and verification data.The findings showed that the implementation of computer asissted instruction at MIN Pahandut and MIN Langkai have been employed, although they still used limited to the special subjects by using the classical instruction model. The implementation of the computer asissted instruction at the both of schools have been agreed with the principle of instruction media selection. There were some problems when employing of CAI as follows: the number of instruction CD and computers were limited, there was no computer lab, and that not all the teacher had the capability in operating computer.Â